Analytical Solution for Waves Propagation in Heterogeneous Acoustic/Porous Media Part I: The 2D Case (Communications in Computational Physics, 2010)
Thanks to the Cagniard-de Hoop's method we derive the solution to theproblem of wave propagation in an infinite bilayered acoustic/poroelastic media, wherethe poroelastic layer is modelled by the biphasic Biot's model. This first part is dedicatedto solution to the two-dimensional problem. We illustrate the properties of thesolution, which will be used to validate a numerical code.